Development and Human Rights in the Middle East and North Africa (MENA) : Challenges and Opportunities - Lind, Lene; Gustafsson, Sara; Raghavan, Vikram (World Bank, Washington, DC, 2012)
Many parts of Middle East and North Africa (MENA) have experienced volatility and fragility due to conflict over the course of the region's long and complex history. These conflicts have had significant impact on economic and human development indicators. Also, and more recently, massive protests and unrest have flared across several parts of the region. In Egypt and Tunisia these protests have led to historic political changes, even as the situation is still unfolding in others. These changes are likely to have significant consequences, especially for citizens' participation and involvement in the development process, which are increasingly articulated through the prism of human rights. This fast brief aims at assisting staff to form a better understanding of these issues. Conflict, as currently witnessed in the MENA region, is not only a tool for destruction and suffering, but also a vehicle for social and political change. Violent conflict, however, prevents the kind of stability necessary for human and economic development and for reaching the overall Millennium Development Goal (MDG) of human security for all. With more than 1,5 billion people living in countries affected by conflict, the World Development Report 2011 (WDR) underlines the negative impact of persistent conflict on a country's or a region's development prospects and notes that no low-income conflict affected state has yet achieved a single MDG.